Micronucleus frequencies in peripheral blood lymphocytes in a Serbian human population exposed to pesticides (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Micronucleus (MN) is a biomarker widely used in biomonitoring studies for determiningthe genetic risk associated with exposure to pesticides. The purpose of this study was toassess damage to the genetic material of workers occupationally exposed to pesticides as detected in micronucleus tests. The research included 119 subjects divided into three groups: a control group of 39 subjects, a group of 40 subjects exposed to pesticides as producers and a group of 40 pesticide applicators in the field. A Mann-Whitney U-test displayed statistically significant differences between the parameter means of all variables, and the control group. Significant differences were observed between males involved in pesticide production and application for the parameter MN4, then between non-smoking producers and applicators regarding parameters MN2, MN3, MN4 and NB, as well as between the control and applicator groups for parameter MN2, and between producers and applicators for parameter MN3. Spearman’s correlation test showed a positive correlation between the frequency of micronuclei and age of respondents, as well as their smoking habits. A statistically significant difference in relation to cytogenetic parameters was detected between the respondents working in pesticide production and those working in the field. The results suggest that applicators in the field do not use adequate personal protective equipment. Regular biological monitoring of workers exposed to pesticides is required.
Keywords: Pesticides; Occupational hazards; Micronucleus test; Serbia